Facies architecture and sequence stratigraphy of Kungurian Amb Formation, western Salt Range, Pakistan - Khawaja Umair Majeed; Syed Kamran Ali; Syed Umair Ali; Muhammad Haris; Raja Qauid Ahmad; Basit Ali Khan; Atif Jamil; Nusrat Nazir (Kuwait Journal of Science)
The Amb Formation of the Permian age is exposed in the Salt Range in the upper Indus basin of Pakistan. This rock unit is mainly composed of sandstone and shale in which three facies (named AF1, AF2, AF3) and five microfacies were distinguished based on field and petrographic study, respectively. Porosity and permeability have changed and exhibit various diagenetic processes. Sequence stratigraphy identifies the zones of all upward concaving cycles and HST. The petrophysical study indicates good reservoir characteristics for the Amb Formation and this can act as reservoir rock in the petroleum system. Fossil assemblages, including Fusulina spp., identified during petrographic analysis indicate an Early Permian age of the Amb Formation in the study area. The multidisciplinary study carried out in the study area allowed us to reconstruct the depositional model for the Amb Formation which occurred in the middle to inner shelf and in a shallow marine environment. Interpretation of well logs of the Dhermund well show good reservoir properties of the Amb Formation including total porosity (13%), effective porosity (9.04%), volume of shale (14.54%), water saturation (34%), hydrocarbon saturation (65%), permeability (121.92 mD), total thickness of the formation (107 m) and net reservoir thickness (13.12m). This research approach of combined field and laboratory stratigraphy and biostratigraphy would be applied in other areas of exposure of the Amb Formation to unravel the age and depositional environment of this formation.